Relationships between athletic ability and academic performance in primary school students: A 3-year follow-up study - Ji, Hao Zong; Bai, Cui Jin; Yun, Yang; Dong, Wu Xiang; Yi, Qian Ze; Ping, Wu Dan; Yi, Tang; Xia, Zheng Hong; Min, Zhang Zhi; Long, Xu Jing; Fei, Zhang Teng; Ji, Wang Jun; et al. (Frontiers in Public Health, 2023)
BACKGROUNDː The aim of this study was to examine whether academic performance is associated with the athletic ability of students in primary school. METHODSːA 3-year follow-up study was conducted with 1131 Chinese students. A sit-up tester and a jump rope tester were used to measure one-minute sit-ups and one-minute jump ropes, respectively. We used the Pittsburgh Sleep Quality Scale and the Beck Depression Inventory to estimate sleep quality and depression levels,with using end-of-semester exams to evaluate student academic performance during the follow-up period. RESULTSːAfter adjusting for confounders, the mean change in Chinese language performance for participants stratified by one-minute sit-ups at baseline was 0.35 (95% CI,-0.37 to 0.76) for level 1(slowest), 0.52 (95% CI,-0.54 to 1.08) for level 2, 1.72 (95% CI,1.14 to 2.30) for level 3(fastest), (P for trend=0. 003); the mean change in math scores was 0.28 (95% CI,-0.50 to 0.95) for level 1 (slowest), 0.95 (95% CI,0.38 to 1.52) for level 2, 1.41 (95% CI,0.82 to 1.99) for level 3 (fastest), (P for trend=0.048). The mean change in foreign language scores was 0.45 (95% CI,-0.99 to -0.93) for level 1 (slowest), -0.14 (95% CI, -0.44 to 0.41) for level 2, 0.69 (95% CI, 0.25 to 1.13) for level 3 (fastest), (P for trend=0.004). the mean change in Chinese language performance for participants stratified by one-minute jump ropes at baseline was 0.30 (95% CI,-0.16 to 0.76) for level 1 (slowest), 1.09 (95% CI,0.42 to 1.76) for level 2, 1.74 (95% CI,1.14 to 2.35) for level 3 (fastest), (p for trend = 0. 001).The mean change in math scores was 0.41 (95% CI, -0.11 to 0.92) for level 1 (slowest), 1.44 (95% CI, 0.69 to 2.19) for level 2, 1.43 (95% CI, 0.76 to 2.10) for level 3 (fastest), (P for trend = 0.019).The mean change in foreign language performance was -0.71 (95% CI, -1.08 to -0.33) for level 1 (slowest), 0.95 (95% CI, -0.40 to 1.50) for level 2, 0.91 (0.41 to 1.41) for level 3 (fastest), (P for trend < 0.001).